From Lyubov Gurevich's Memoirs about the Journal “Severny Vestnik”. Part Two - Margarita M. Pavlova (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2021)
The journal “Sevemy Vestnik”, around which relatively young Petersburg writers — A. Volynsky, N. Minsky, D. Merezhkovsky and Z. Gippius, F. Sologub — were grouped in the last years of the 19th century, was of exceptional importance for the early stage of Russian Symbolism. The article continues the previously begun publication of new materials from the archive of the publisher (since 1891) of the “Severny Vestnik”, Lyubov Gurevich. Two documents from the funds of the RGALI and the Manuscript Division of the IRL RAS — “Lovely Memories” and a note on the reorganization of the journal (1897–1898) — are presented. They are a kind of factual basis and addition to her article “Symbolism of the 1890s and the journal 'Severny Vestnik'” (presented in the first part of the publication: Literaturnyi fakt, no. 1 (19), 2021). Gurevich tells about the financial, organizational and censorship difficulties of keeping the journal and about complicated relationships in the circle of its authors and editors. The appendix contains Gurevich’s letter dated 1891 to her father where she admits that she is attracted by journalism and literary work “more than anything else”, and asks for financial help to buy out the collapsing journal and become the publisher of “Severny Vestnik” herself. Documents introduced into scientific circulation allow expanding the range of sources for studying the history of journalism and early Russian modernism.